RELATIONSHIP BETWEEN NUMERICAL SKILLS, INTEREST OF LEARNING, AND ATTENTION OF PARENTS WITH THE LEARNING OUTCOMES OF MATHEMATICS STUDENTS - Mailan 'Aziziyah; Sunaryo Sunaryo (Universitas Ahmad Dahlan, 2017)
The result of low mathematics learning is associated with many factors. Numerical ability, learning and attention from their parents are some of the factors that were related to the students' mathematics learning outcomes. Therefore, this study was conducted to determine whether there is a positive relationship between numerical ability, interest in learning, and attention parents with mathematics learning outcomes eighth-grade students of SMP Unggulan 'Aisyiyah Bantul regency in Odd Semester in Academic Year of 2016/2017. The population in this research is class VIII SMP Unggulan 'Aisyiyah Bantul regency in Odd Semester in Academic Year of 2016/2017, which consists of classes that Maryam and Hafsah totaling 41 students. Research carried out the study population. The data collection technique using questionnaires to obtain data on interest in learning, and attention from their parents, as well as test methods to obtain data of numerical ability and mathematics learning outcomes. Test instruments research: validity, different power, and reliability testing. Prerequisite test analysis covering the normality test, linearity, and independent testing. Analyzed using product-moment and multiple linear regression analysis. The results showed that there was a positive relationship between the numerical ability, interest in learning, and attention parents with mathematics learning outcomes eighth-grade students of SMP Unggulan 'Aisyiyah Bantul regency in Odd Semester in Academic Year of 2016/2017. This is shown by R = 0,5341 and R2 = 0,2853 with , with SR = , SR = and SR = 50,0699 , SE = , SE = and SE = .